Pathophysiology of Long Non-coding RNAs in Ischemic Stroke - Ren, Weimin; Yang, Xiaobo (Frontiers in Molecular Neuroscience, 2018)
Stroke is a neurological disease with high disability and fatality rates, and ischemic stroke accounts for 75% of all stroke cases. The underlying pathophysiologic processes of ischemic stroke include oxidative stress, toxicity of excitatory amino acids, excess calcium ions, increased apoptosis, and inflammation. Long non-coding RNAs (lncRNAs) may participate in the regulation of the pathophysiologic processes of ischemic stroke as indicated by altered expression of lncRNAs in blood samples of acute ischemic stroke patients, focal ischemia animal models and oxygen-glucose deprivation (OGD) cell models. Because of the potentially important role , lncRNAs might be useful as biomarkers for the diagnosis, treatment and prognosis of ischemic stroke. This article reviews the functions of lncRNAs in different pathophysiology events of ischemic stroke with a focus on specific lncRNAs that may underlie ischemic stroke pathophysiology and that could therefore serve as potential diagnostic biomarkers and therapeutic targets.